2022-RA-430-ESGO Prognostic value of systemic inflammatory markers in cervical cancer. (20th October 2022) - Vitkauskaite, Agne; Celiesiute, Joana; Vaitkiene, Daiva
Abstract : Introduction/Background: There is increasing evidence that the host inflammatory response plays crucial role in the development and progression of cervical cancer (CC). It might be that cancer is associated not only with inflammation at the site of the lesion, but also with the overall systemic immune response. The aim of the study was to evaluate prognostic value of systemic inflammatory markers of CC and healthy controls. Methodology: In this prospective study, we examined levels of 7 different cytokines (TNF-α, IFN-β, IFN-γ, IL-1β, IL-6, LPC2 ir TREM-1) by using Magnetic bead-based multiplex (Luminex Corporation, United States) assay in sera of 94 squamous cell CC patients treated in Lithuanian University of Health Sciences Hospital Kaunas Clinics Obstetric and Gynaecology department and 88 healthy (NILM) women. The blood samples was collected before any treatment or diagnostic procedures. Results: CC patients prognostic value was found of TNF-α > 17.6 pg/ml; IFN-β > 79.01 pg/ml; IFN-γ > 1972.74 pg/ml; IL-1β > 145.3 pg/ml; IL-6 > 17.41 pg/ml; LCN2 > 23721.5 pg/ml and TREM-1 > 355.6 pg/ml. Based on the data set, we can predict a finite multivariate model of binary logistic regression analysis. CC the odds ratio is higher than 3.4, if LPN2 > 23721.5 pg/ml, CC the odds ratio is higher than 6.0, if TREM > 355.6 pg/ml and CC the odds ratio is higher than 11.4, if IL-6 > 14.4 pg/ml. Conclusion: Monitoring blood levels of LPC2, TREM-1 and IL-6 may be important in predicting cervical cancer especially in risk patients.